A reservoir model for geothermal energy production from the Middle Devonian Slave Point Formation. (July 2021) - Renaud, Evan; Weissenberger, John A.W.; Harris, Nicholas B.; Banks, Jonathan; Wilson, Brandon
Abstract: Clarke Lake is a depleted gas field developed in carbonate platform deposits of the Slave Point Formation (Middle Devonian) in northeastern British Columbia, Canada. The field displays anomalously high reservoir temperature (≥100 °C) and strong water drive, making it a candidate for repurposing as a source of geothermal power. Porous and permeable reservoir developed near the platform margin through the hydrothermal alteration of host limestone to dolomite. A depositional model provides a basis for mapping the dolomite reservoir properties. Facies analysis combined with porosity and permeability measurements are applied to flow simulations to test how reinjected water would affect geothermal power production. Nine depositional facies and two diagenetic facies are identified: the former based on bioclast assemblages, rock types, texture and composition; and the latter based on rock fabric and the extent of alteration to dolomite. These facies were deposited within lagoonal, reef-flat, shoal, reef margin and foreslope settings associated with a rimmed carbonate platform and can be separated into stratigraphic successions that influenced dolomitization: an initial shoal unit, S1, three subsequent reef units, R1, R2, R3, and terminal shoal units of D1, D2 and D3. Shoal units were deposited in the transgressive systems tracts, whereas reef growth units were deposited in the highstand systems tracts. Dolomitized lagoonal, reef flat, reef margin and shoal lithologies show enhanced porosity and permeability due to dissolution of stromatoporoid bioclasts, forming mouldic and vuggy porosity. Diagenetic facies show high permeability due to fractures but reduced porosity as a result of precipitation of porosity-occluding dolomite, fluorite, and sulphide minerals. High quality reservoir zones occur primarily at the reef margin, caused by fabric-selective hydrothermal alteration of carbonate sediments near the contact with shales of the Horn River and Muskwa formations. Numerical modelling of geothermal injection and production scenarios shows that thermal breakthrough from injection wells to producing wells presents a negligible risk to estimated power productions, with efficiencies being reduced by 10–15% compared to scenarios that assume no thermal breakthrough. Permeable, fractured diagenetic and reef front facies are suitable targets for geothermal fluid production. Highlights: Depleted oil and gas reservoirs repurposed as sources of geothermal power. Characterizing a dolomite reservoir develped within a rimmed carbonate platform. Petrophysical analysis of hydrothermal dolomite. Sedimentary hosted geothermal reservoirs.